Recognizing & engaging employees for dummies - Nelson, Bob, 1956- (Tantor Audio, 2019)
Recognizing and Engaging Employees for Dummies gives you the tools and information you need to improve morale, productivity, and personal achievement with a successful employee recognition program. Written by a world-leading authority in employee recognition, this book walks you step-by-step through the design and implementation process and describes the incentives that work, the behaviors to reward, and the mechanisms that must be in place for the program to be effective in the long term. You'll learn how to pinpoint the places where engagement and recognition could improve the bottom line, and how to structure the reward for optimal balance between motivational, financial, and organizational effectiveness. With clear explanations and a fun, friendly style, this book is your quick and easy guide to boosting productivity, profit, and customer satisfaction. Happy employees are productive employees. They get results. They innovate. They are the force behind the advancement of industries. Effective employee recognition programs are self-sustaining motivational tools that keep the fire lit. If you're ready to spark the flame, Recognizing and Engaging Employees for Dummies is the ideal guide for designing, implementing, and maintaining the program your employees have been waiting for.